2017
DOI: 10.1038/s41467-017-02191-y
|View full text |Cite
|
Sign up to set email alerts
|

Albumin/vaccine nanocomplexes that assemble in vivo for combination cancer immunotherapy

Abstract: Subunit vaccines have been investigated in over 1000 clinical trials of cancer immunotherapy, but have shown limited efficacy. Nanovaccines may improve efficacy but have rarely been clinically translated. By conjugating molecular vaccines with Evans blue (EB) into albumin-binding vaccines (AlbiVax), here we develop clinically promising albumin/AlbiVax nanocomplexes that self-assemble in vivo from AlbiVax and endogenous albumin for efficient vaccine delivery and potent cancer immunotherapy. PET pharmacoimaging,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
217
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(238 citation statements)
references
References 66 publications
3
217
0
Order By: Relevance
“…Among recent preclinical studies dealing with peptide-based anticancer vaccines, we found of particular interest the works of: (1) Zhu and colleagues (from the National Institutes of Health, Bethesda, MD, USA), who developed self-assembling albumin-vaccine nanocomplexes that reportedly enable superior delivery and mediated robust therapeutic effect against transplantable tumors growing in immunocompetent mice, especially when combined with immune checkpoint blockers and chemotherapy; 94 (2) Gall et al (from the MD Anderson Cancer Center, Houston, TX, USA), who unveiled a Fc receptor-mediated mechanism whereby the FDA-approved HER2-targeting mAB trastuzumab favors the uptake of a HER2-targeting vaccine by DCs, resulting in efficient cross-presentation of its immunodominant epitope in vivo and robust therapeutic effects against breast carcinoma; 171 (3) Tsuruta et al (from Kumamoto University, Kumamoto, Japan), who developed DEP domain containing 1 (DEPDC1)- and M-phase phosphoprotein 1 (MPHOSPH1)-derived synthetic long peptides (SLPs) that efficiently induce both helper T (T H ) cells and CTLs in vitro and in vivo ; 172 (4) Petrizzu and collaborators (from the Istituto Nazionale per lo Studio e la Cura dei Tumori, Naples, Italy), who showed that metronomic chemotherapy plus a PD-1-targeting immune checkpoint blocker are highly efficient in potentiating the antitumor effects of a multi-peptide vaccine in a mouse model of melanoma; 173 and (5) Tanaka and co-workers (from the Yamaguchi University, Ube, Japan), who demonstrated that miR-125b-1 and miR-378a expression levels may be harnessed to predict the efficacy of peptide-based vaccination against colorectal carcinoma. 174 …”
Section: Literature Updatementioning
confidence: 99%
“…Among recent preclinical studies dealing with peptide-based anticancer vaccines, we found of particular interest the works of: (1) Zhu and colleagues (from the National Institutes of Health, Bethesda, MD, USA), who developed self-assembling albumin-vaccine nanocomplexes that reportedly enable superior delivery and mediated robust therapeutic effect against transplantable tumors growing in immunocompetent mice, especially when combined with immune checkpoint blockers and chemotherapy; 94 (2) Gall et al (from the MD Anderson Cancer Center, Houston, TX, USA), who unveiled a Fc receptor-mediated mechanism whereby the FDA-approved HER2-targeting mAB trastuzumab favors the uptake of a HER2-targeting vaccine by DCs, resulting in efficient cross-presentation of its immunodominant epitope in vivo and robust therapeutic effects against breast carcinoma; 171 (3) Tsuruta et al (from Kumamoto University, Kumamoto, Japan), who developed DEP domain containing 1 (DEPDC1)- and M-phase phosphoprotein 1 (MPHOSPH1)-derived synthetic long peptides (SLPs) that efficiently induce both helper T (T H ) cells and CTLs in vitro and in vivo ; 172 (4) Petrizzu and collaborators (from the Istituto Nazionale per lo Studio e la Cura dei Tumori, Naples, Italy), who showed that metronomic chemotherapy plus a PD-1-targeting immune checkpoint blocker are highly efficient in potentiating the antitumor effects of a multi-peptide vaccine in a mouse model of melanoma; 173 and (5) Tanaka and co-workers (from the Yamaguchi University, Ube, Japan), who demonstrated that miR-125b-1 and miR-378a expression levels may be harnessed to predict the efficacy of peptide-based vaccination against colorectal carcinoma. 174 …”
Section: Literature Updatementioning
confidence: 99%
“…Moreover, NP‐based delivery systems can effectively target tumors via enhanced permeability and a retention effect or overexpressing receptors . Therefore, the accumulation, permeation and cellular uptake efficiency can be improved greatly by tumor microenvironment‐responsive nanovectors …”
Section: Tumor Microenvironment‐targeted Rna Interference Strategy Fomentioning
confidence: 99%
“…45 Therefore, the accumulation, permeation and cellular uptake efficiency can be improved greatly by tumor microenvironment-responsive nanovectors. [46][47][48] NP-based approaches have been demonstrated as an effective strategy for stimulating a targeted and tumor microenvironmentsensitive immune response. [48][49][50][51][52] Researchers have designed versatile nanoformulations for the tumor-targeted and stimulusspecific delivery of immune modulators to the tumor tissues/cells (Table 1).…”
Section: Tumor Microenvironment-targeted Rna Interference Strategy mentioning
confidence: 99%
See 1 more Smart Citation
“…125129 Researchers recently reported a cancer vaccine using albumin as a carrier showing great promise in in vivo trials. 130 Many more albumin-based approaches are currently in clinical trials. Taking advantage of natural protein aggregation processes may indeed provide a key to avoiding the challenges of heterogeneous distributions in synthetic and natural drug delivery materials.…”
Section: Introductionmentioning
confidence: 99%